Handout : Internal Combustion Engines - ZAHZOUH Zoubir (Souk ahras University, 2026)
This course handout provides a comprehensive technical and thermodynamic study of internal combustion engines (ICE), structured into five main chapters. It begins with an overview of engine architecture, detailing stationary and moving parts, alongside a rigorous classification of heat engines based on ignition methods (spark-ignition/compression-ignition) and operating cycles. The second part focuses on thermodynamics, analyzing fundamental theoretical cycles such as the Beau de Rochas (Otto), Diesel, and Sabathé cycles. The author then examines the actual engine cycle, highlighting deviations from theoretical models, including heat losses, valve timing, and effective efficiencies. Kinematic and dynamic aspects are also covered, including calculations for piston motion (displacement, velocity, acceleration) and the balancing of rotating masses. Finally, the handout addresses overall engine performance, covering advanced concepts such as supercharging, volumetric efficiency, and modern direct injection systems for both gasoline and diesel engines.
1. Generalities: Architecture, components, and classification. 2. Thermodynamics: Study of theoretical cycles and combustion. 3. Real Cycle: Analysis of (P,V) diagrams and efficiencies. 4. Dynamics: Kinematics of the connecting rod-crank system and balancing. 5. Performance: Specific fuel consumption, turbocharging, and direct injection.